2021
DOI: 10.3389/fphar.2021.747625
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol on the Metabolic Reprogramming in Liver: Implications for Advanced Atherosclerosis

Abstract: Background/Aims: Atherosclerosis (AS) is one of the major leading causes of death globally, which is highly correlated with metabolic abnormalities. Resveratrol (REV) exerts beneficial effects on atherosclerosis. Our aim is to clarify the involvement of liver metabolic reprogramming and the atheroprotective effects of REV.Methods: ApoE-deficient mice were administered with normal diet (N), high-fat diet (H), or HFD with REV (HR). Twenty-four weeks after treatment, Oil Red O staining was used to assess the seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…AS is closely linked with system metabolic abnormity [39, 40]. To confirm the impact of KLF7 on the metabolism of AS mice, we detected metabolic indexes of HFD mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AS is closely linked with system metabolic abnormity [39, 40]. To confirm the impact of KLF7 on the metabolism of AS mice, we detected metabolic indexes of HFD mice.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, recruitment of KLF4 reduces the AS lesion area and delays the AS development [47, 48]. In addition, AS plaque pathogenesis is also associated with system metabolic abnormality [39, 40]. Therefore, we explored the impact of KLF7 on lipid and glucose metabolism in AS, and our subsequent experiments revealed that KLF7 overexpression increased HDL-C and decreased TC, TG, LDL-C, FPG, and glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Despite advancements in the study of atherosclerosis, the field lacks a systemic understanding of mechanisms of the disease, particularly in molecular regulators with significant pathophysiological commonalities between intracellular proteome homeostasis and atherosclerosis. Growing evidence supports the concept that aberrations in the metabolic programming contribute to the development of atherosclerosis (16,17). Chronic inflammation induced by metabolic perturbance is also associated with disordered proteomic stability in atherosclerosis (18).…”
Section: Etiology Of Atherosclerosismentioning
confidence: 89%
“…However, as the population greatest at risk of invasive candidiasis are those with hematologic malignancies, this strategy raises safety concerns. While probiotics can act as PPAR-γ agonists (Hasan, Rahman et al 2019) and reduce Candida colonization (Archambault and Dongari-Bagtzoglou 2022), probiotics or full fecal microbiota transplants are not typically considered in hematologic malignancy due to safety concerns over infections stemming from the deleterious effects of chemotherapy (Ma, Li et al 2021). Additionally, in patients on antibiotic prophylaxis, probiotics or fecal microbiota transplants are not likely to engraft successfully.…”
Section: Discussionmentioning
confidence: 99%